PENGARUH PROFITABILITAS, LEVERAGE, DAN INTENSITAS MODAL TERHADAP TAX AVOIDANCE - Elvira, Dilla; Samrotun, Yuli Chomsatu (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
Taxes are binding and must be met by every individual or state entity. Taxes play a crucial role in increasing national income, which is directly related to national growth. Therefore, it is necessary to examine the factors that influence tax evasion. This research investigates the influence of profitability, leverage, and capital intensity on tax avoidance among transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The sample was selected using a purposive sampling technique, resulting in 12 companies over a three-year observation period (36 data points). The data was analyzed using multiple linear regression. Several assumptions were met, including freedom from multicollinearity, identical residuals, independence, and a normal distribution. The normality assumption was not met, necessitating outlier elimination. After conducting an outlier elimination process, the final dataset consisted of 33 observations. The findings reveal that both profitability and leverage have a positive impact on tax avoidance, whereas capital intensity does not exhibit a statistically significant effect.